CLUSTERING OF CITIES AND REGENCIES IN WEST NUSA TENGGARA BASED ON WELFARE INDICATORS: A HIERARCHICAL AGGLOMERATIVE APPROACH - Hesikumalasari; Sudarsono; Siti Husna Ainu Syukri (Universitas Islam Negeri Mataram, 2026)
Community welfare is a primary development goal emphasized in the Sustainable Development Goals (SDGs) and Indonesia’s RPJPN. However, disparities in welfare persist in regions such as West Nusa Tenggara (NTB), which consistently ranks below the national average in indicators such as poverty, education, and health. This condition underscores the need for data-driven approaches to understand regional characteristics and develop more targeted policies. This study aims to clustering Cities/Regencies in West Nusa Tenggara (NTB) Province based on people's welfare indicators. These indicators are indicators of people's welfare that represent aspects of population, health, education, employment, level and pattern of consumption, poverty and housing. The objects of observation are all Cities/Regencies in the province of NTB consisting of 10 Cities/Regencies, namely Bima City, Central Lombok Regency, East Lombok Regency, North Lombok Regency, West Lombok Regency, Mataram City, Sumbawa Regency, West Sumbawa Regency, Dompu Regency and Bima Regency. The data collection method used is the documentation method, which is obtained from the publication of Central Statistics Agency of NTB for 2022. The data analysis technique used in this study is quantitative data analysis using cluster analysis. The cluster analysis method used is the agglomerative hierarchical technique consisting of average linkage, single linkage, complete linkage, centroid, median and wards method. Based on the analysis that has been carried out, it is known that the grouping of Cities/Regencies in the NTB Province showed various clusters of each method. The optimal group is obtained by using Davies-Bouldin Index value consists of 5 clusters using average linkage, single linkage, centroid and median method; six Regencies joined in cluster 1 which are West Lombok, Central Lombok, East Lombok, Sumbawa, Dompu and Bima, West Sumbawa Regency in cluster 2, North Lombok Regency in cluster 3, Mataram City in cluster 4 and Bima City in cluster 5. The grouping results are expected to be input to the Government to plan strategic programs according to the different characteristics of each cluster to improve the welfare of the people of NTB. Keywords: Clustering; Welfare; Indicator; Cluster Analysis; Agglomerative Hierarchical